Genetic Variability, Heritability, and Correlation of Some Agronomical Characters of Soybean Varieties - Kuswantoro, Heru; Artari, Rina; Rahajeng, Wiwit; Ginting, Erliana; Supeno, Agus (Biosaintifika: Journal of Biology & Biology Education, 2018)
Genetic diversity and inheritance of the traits determine the success of the breeding program. Analysis of genetic variability and heritability assist breeders to decide a strategy and appropriate selection criteria that will be used to repair the desired character. The purpose of this study was to obtain information about genetic diversity, heritability and correlation of nine agronomic characters of soybean varieties. The materials were 16 soybean varieties that arranged in a randomized block design with three replications. The results showed that days to flowering, number of branches per plant, number of reproductive nodes, number of unfilled pods per plant, weight of 100 seeds, and grain yield revealed broad CVG (Genetic Coeffiecient of Variance), whereas the days to maturity, plant height, number of pods per plant had a narrow CVG. CVP (Phenotypic Coeffiecient of Variance) value higher than the value of CVG on all the observed characters with a slight difference, except for grain yield. The broad sense heritability varied from low (seed yield), medium (the number of branches, number of reproductive nodes, number of pods and the number of unfilled pods), and high (days to flowering, days to maturity, plant height, and weight of 100 seeds). Characters of days to flowering and weight of 100 seeds are effectively used as selection criteria because they had a broad CVG and high heritability. Correlation of all yield components to the seed yield was not significant, and negatively correlated to weight of 100 seeds. Variety with higher plant height tended to have a higher number of branches, reproductive nodes and filled pod per plant.